Pemberhentian Dengan Tidak Hormat Pegawai Aparatur Sipil Negara (Tinjauan Undang-Undang No. 5 Tahun 2014) - Rusnin Rusnin (Jurnal Transformasi Administrasi, 2019)
Implementation of dismissal of sanctions against civil servants who commit criminal acts of this position need to be seen and assessed suitability of its application based on the rules governing it, this will have an impact on legal certainty of its status as a civil servant and the rights that must be accepted as civil servants during the legal process is still ongoing, as well as legal certainty against the decision charged to the civil servant if he has permanent legal force. Article 87 paragraph (4) letter b of Act Number 5 of 2014 concerning ASN states that: Civil servants are dismissed without respect because of: committing fraud against Pancasila and the 1945 Constitution of the Republic of Indonesia; sentenced to prison or confinement based on a court ruling that has permanent legal force because of a crime in a position or criminal offense that has something to do with a general duty or crime; The research method used is legal research using empirical juridical methods. Empirical juridical approach. The results of the study show the position of civil servants who have been sentenced for committing criminal offenses can be concluded as follows: Against a legal status for civil servants who have been sentenced for committing crimes as regulated in Article 87 paragraph (4) letter b of Law Number 5 In 2014 about the Civil Servants of the State Civil Servants were dismissed not honorably because: So that if we look at the conditions stated above will be terminated from their office and the civil servants' personal data will be deflected from the Ministry of Personnel data base so we can draw conclusions. In the event that a legal legal status is clear to civil servants who commit office crimes, they will be dismissed.